Comparing quantitative and qualitative survey data - Rolf Schenker (ETH Zurich, KOF Swiss Economic Institute, 2007)
This paper compares quantitative and qualitative data on firm level. The data is taken from two Swiss investment surveys. This has not yet been done in the literature. We will see that the mean change in investment of firms planning to increase (decrease) investments is positive (negative). In contrast, the mean change in investment of firms indicating no change is indeed virtually zero. Carlson & Parkin (1975) assume the quantitative observations to follow a normal distribution. Other research (e.g. Dasgupta & Lahiri 1992) has been done assuming other distributions. In this paper we show that the micro data does not follow a normal, logistic or exponential distribution. Furthermore, we adopt the response functions presented by Ronning (1984) to the investment data. They help us to determine the share of firms giving the different qualitative statement for every instance of the quantitative data. We will show that with larger (smaller) quantitative changes, more firms give positive (negative) qualitative statements.
Keywords: C5; E22; C42; 330; Response Functions; Investment survey; Qualitative response; Contingency Table; Mikrodaten; Investition; Statistische Verteilung; Qualitatives Verfahren; Schweiz